A Complete and Low-Cost Cardiac Optical Mapping System in Translational Animal Models - Marina-Breysse, Manuel; García-Escolano, Alba; Vila-García, Joaquín; Reale-Nosei, Gabriel; Alfonso-Almazán, José M.; Yan, Ping; Quintanilla, Jorge G.; Loew, Leslie M.; Lee, Peter; Filgueiras-Rama, David (Frontiers in Physiology, 2021)
Clinicians, biologists, physicists, engineers and computer scientists are coming together to better understand heart disease, which is currently the leading cause of death globally. Optical mapping, a high-speed fluorescence imaging technique that visualizes and measures key cardiac parameters such as action potentials, cytosolic calcium transients and fibrillation dynamics, is a core research tool that has arisen from such interdisciplinary collaborations. In an effort to broaden its use, especially among clinical scientists and students, we developed a complete and low-cost optical mapping system, including a constant-flow Langendorff perfusion system, which minimizes the economic threshold to widespread use of this powerful tool in cardiac electrophysiology research. The system described here provides high spatiotemporal resolution data about action potentials, intracellular calcium transients and fibrillation wave dynamics in isolated Langendorff-perfused hearts (pigs and rabbits), relevant for translational research. All system components and software elements are fully disclosed with the aim of increasing the use of this affordable and highly versatile tool among clinicians, basic scientists and students wishing to tackle their own research questions with their own customizable systems.